Kualitas Fisik Daging Sapi Peranakan Ongole dengan Pemberian Asam Askorbat dan Penyimpanan pada Suhu 50C - E P Samodra; H Cahyono (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2010)
The research was conducted to investigate the effect of soaking meat of Peranakan Ongole cattle with ascorbic acid and storage duration at 50C on physical quality of meat. The experiment was done in Complete Randomised Design by factorial 3 x 3. First factor was ascorbic acid with 3 levels (0%, 5%, 1%), and second factor is storage duration with 3 levels (0, 5, and 6 days). Variables that were measured: tenderness, cooking loss, water holding capacity and pH. Data were analyzed by variance analysis and the significant result were tested by Duncan’s test. Tenderness average for ascorbic acid ranging between 1,60 – 1,62 kg/cm2, and for storage duration was increased from 1,83 to 1,38 kg/cm2. Cooking loss average for ascorbat acid ranged from 43,33 to 44,89%, and for storage duration increased from 40,00 to 47,00%. Water holding capacity average for ascorbic acid ranging between 32,88 – 33,65%, but for storage duration decreased from 34,61 to 32,32%. The pH average for ascorbic acid ranging from 5,99 to 6,16, and increased for storage duration from 6,43 to 5,84. It can be concluded that physical quality of beef cattle was not affectedbay ascorbic acid up to 1%, but was significantly decreased by storage duration (p<0,05).Key words: Pernakan Ongole meat, ascorbat acid, storage time